2018
DOI: 10.20506/37.3.2897
|View full text |Cite
|
Sign up to set email alerts
|

Study on seroprevalence and serotyping of foot and mouth disease in Chad

Abstract: Foot and mouth disease (FMD) is a highly contagious viral disease that affects all Artiodactyla. Seven immunologically distinct serotypes of FMD virus (FMDV) exist. In Chad, although FMD is included in the list of diseases monitored by the Chadian Animal Disease Surveillance Network (REPIMAT), the epidemiological situation remains unclear. A serological survey was conducted in the cattle population in eight of the nine administrative regions of the country (those regions with the highest cattle densities), to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Studies in Chad, Niger and Uganda have shown that increased density of cattle and small ruminants is a risk factor of FMD spread (Munsey et al, 2019;Ouagal et al, 2018;Souley Kouato et al, 2018).…”
Section: Density Of Ruminant Populationmentioning
confidence: 99%
“…Studies in Chad, Niger and Uganda have shown that increased density of cattle and small ruminants is a risk factor of FMD spread (Munsey et al, 2019;Ouagal et al, 2018;Souley Kouato et al, 2018).…”
Section: Density Of Ruminant Populationmentioning
confidence: 99%
“…Foot-and-mouth disease virus (FMDV) is a tiny, non-enveloped, proactive, single-stranded RNA that belongs to the genus Aphthovirus under the Picornaviridae family (Malik et al, 2017). Seven immunologically unique FMDV serotypes such as A, O, C, Asia1, SAT-1, SAT-2, and SAT-3 are found worldwide (Ouagal et al, 2018). Except from Asia1, the other six FMDV serotypes were present in the African continent from 1993 to 2012 (Lloyd-Jones et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of FMD virus transmission is most likely related to animal mobility (Bertram, Bravo, et al, ; Bertram, Delgado, et al, ). In Chad, four serotypes have been identified: O, A, SAT1 and SAT2 (Gueme, ; Ouagal et al, , ; Ouagal, Hendrikx, Saegerman, & Berkvens, ). The circulation of these serotypes was reported in countries neighbouring Chad, such as Sudan, Cameroon, Niger and Nigeria (Abu Elzein, ; Bertram, Bravo, et al, ; Bertram, Delgado, et al, ; Ehizibolo et al, , ; Habiela, Alamin, Alamin, Raouf, & Ali, ; Habiela, Ferris, et al, ; Knowles, Bachanek‐Bankowska, et al, ; Kouato, Elliot, et al, ; Kouato, Souley, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In Chad, four serotypes have been identified: O, A, SAT1 and SAT2 (Gueme, 1998;Ouagal et al, 2018Ouagal et al, , 2017Ouagal, Hendrikx, Saegerman, & Berkvens, 2010). The circulation of these serotypes was reported in countries neighbouring Chad, such as Sudan, Cameroon, Niger and Nigeria (Abu Elzein, 1983;Bertram, Bravo, et al, 2018;Bertram, Delgado, et al, 2018;Ehizibolo et al, 2017aEhizibolo et al, , 2017bHabiela, Alamin, Alamin, Raouf, & Ali, 2010;Habiela, Ferris, et al, 2010;Kouato, Elliot, et al, 2018;Kouato, Souley, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation